Difference Between Signet Ring Cell Gastric Cancers and Non-Signet Ring Cell Gastric Cancers: A Systematic Review and Meta-Analysis - Zhang, Chi; Liu, Ran; Zhang, Wei-Han; Chen, Xin-Zu; Liu, Kai; Yang, Kun; Chen, Xiao-Long; Zhao, Lin-Yong; Chen, Zhi-Xin; Zhou, Zong-Guang; Hu, Jian-Kun (Frontiers in Oncology, 2021)
Background: There is controversy about the characteristics and prognostic implications of signet ring cell gastric cancers and non-signet ring cell gastric cancers. Objective: This study aims to evaluate clinicopathological characteristics and prognoses of signet ring cell carcinoma (SRCC) and non-signet ring cell carcinoma (NSRCC) of stomach. Methods: Studies compared between SRCC and NSRCC of the stomach after gastrectomy and published before September 1st, 2020, in the PubMed, Cochrane, and Embase databases, were identified systematically. Results: A total of 2,865 studies were screened, and 36 studies were included, with 19,174 patients in the SRCC group and 55,942 patients in the NSRCC group. SRCC patients were younger in age (P < 0.001), less likely to be male patients (P < 0.001), more afflicted with upper third lesions (P < 0.001), and presenting with more Borrmann type IV tumors (P = 0.005) than NSRCC patients. Lymph nodes metastasis was similar between SRCC and NSRCC patients with advanced tumor stage (OR: 0.86, 95% CI: 0.67–1.10, P = 0.23), but lower in the SRCC than NSRCC patients with early tumor stage (OR: 0.73; 95% CI: 0.56–0.98, P = 0.02). SRCC patients had comparable survival outcomes with NSRCC patients for early gastric cancers (HR: 1.05, 95% CI: 0.65–1.68, P < 0.001) but had significantly poor prognosis for patients with advanced tumor stage (HR: 1.50, 95% CI: 1.28–1.76, P < 0.001). Conclusions: Signet ring cell carcinomas of the stomach are an increasingly common histopathological subtype of gastric cancers. These kinds of patients tend to be younger in age and more often female. Although, signet ring cell gastric cancer is a negative prognostic factor for patients with advanced stage. The difference is that for early stage of signet ring cell gastric cancers, it has low lymph nodes metastasis rate and comparable prognosis with non-signet ring cell cancers.